Improvement of Moisture Susceptibility for Asphalt Mixture with Ceramic Fiber (Journal of Engineering, 2023)
Moisture damage is one of the most significant troubles that destroy asphaltic pavement and reduces road serviceability. Recently, academics have noticed a trend to utilize fibers to enhance the efficiency of asphalt pavement. This research explores the effect of low-cost ceramic fiber, which has high tensile strength and a very high thermal insulation coefficient, on the asphalt mixture's characteristics by adding three different proportions (0.75%, 1.5%, and 2.25%). The Marshall test and the Tensile Strength Ratio Test (TSR) were utilized to describe the impact of ceramic fiber on the characteristics of Marshall and the moisture susceptibility of the hot mix asphalt mixture. The Field Emission Scanning Electron Microscopy (FE-SEM) analysis was used to investigate ceramic fibers' microscopic structure and clarify the mechanics of their improved behavior and their distribution within the asphalt concrete mixture. The results showed that the incorporation of ceramic fibers improved the Marshall properties and the asphalt mixture's susceptibility to moisture damage with an optimum fiber content equal to 1.5%, where Marshall stability increased by 39.04%, and the TSR increased by 11.06% at this content compared with the control asphalt mixture.